Encountering the New Testament a historical and theological survey - Elwell, Walter A. 1937-; Yarbrough, Robert W. 1953- (Grand Rapids, MI Baker Academic, a division of Baker Publishing Group, 2022)
"Two experienced classroom teachers offer a new edition of their bestselling and award-winning New Testament survey"--
Includes index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Introductions